2019
DOI: 10.1002/mgg3.714
|View full text |Cite
|
Sign up to set email alerts
|

Three GLI2 mutations combined potentially underlie non‐syndromic cleft lip with or without cleft palate in a Chinese pedigree

Abstract: Background Nonsyndromic cleft lip with or without cleft palate (NSCL/P) is the most common craniofacial birth defect. Its etiology is complex and it has a lifelong influence on affected individuals. Despite many studies, the pathogenic gene alleles are not completely clear. Here, we recruited a Chinese NSCL/P family and explored the candidate causative variants in this pedigree. Methods We performed whole‐exome sequencing on two patients and two unaffected subjects of this family. Variants were screened based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 54 publications
1
14
0
Order By: Relevance
“…The findings supported the role of CLPTM1(3), NECTIN1 (19), OFC1 (22), SPRY2 (23), THADA (24), SHTN1 (54), NOGGIN (27), TPM1 (30), GREM1 (31), PAX7 (34), SHH (36), SIX3 (37), BRIP1(BACH1) (38), BRCA1 (40), MAFB (26), FOXE1 (42), AXIN2 (43), SNAI1 (46), BRCA2 (40), GLI2 (48), GRHL3 (49), COL21A1 (50), WNT5A (51), TOX3 (52), and SOX9 (52) in the development of a CL ± P malformative phenotype. The findings also revealed that GAD1 (28), ARHGAP29 (39), and DVL2 (43) were regulatory proteins essential for proper development of the face.…”
Section: Genes Associated With Orofacial Closure Defectssupporting
confidence: 59%
See 1 more Smart Citation
“…The findings supported the role of CLPTM1(3), NECTIN1 (19), OFC1 (22), SPRY2 (23), THADA (24), SHTN1 (54), NOGGIN (27), TPM1 (30), GREM1 (31), PAX7 (34), SHH (36), SIX3 (37), BRIP1(BACH1) (38), BRCA1 (40), MAFB (26), FOXE1 (42), AXIN2 (43), SNAI1 (46), BRCA2 (40), GLI2 (48), GRHL3 (49), COL21A1 (50), WNT5A (51), TOX3 (52), and SOX9 (52) in the development of a CL ± P malformative phenotype. The findings also revealed that GAD1 (28), ARHGAP29 (39), and DVL2 (43) were regulatory proteins essential for proper development of the face.…”
Section: Genes Associated With Orofacial Closure Defectssupporting
confidence: 59%
“…A study conducted on Gli2 in 2019 among Chinese people found the mutation c. 2684C > T_p. Ala895Val plays a role in the pathogenesis of NSCL/P (48).…”
Section: Genes Associated With Orofacial Closure Defectsmentioning
confidence: 99%
“…In our previous work involving identification of the genetic mutations underlying CL/P, 10 , 17 , 18 many variants were left after the traditional screening process, and a manual literature search was required to identify the candidate(s). In this study, we employed a web crawler strategy for the first time to narrow down the list of variants.…”
Section: Discussionmentioning
confidence: 99%
“…We reviewed the literature for comprehensive phenotypic descriptions of individuals with confirmed pathogenic (a) intragenic GLI2 variants and (b) chromosome 2q14.2 deletions encompassing only GLI2 . We re‐evaluated the pathogenicity of previously published GLI2 missense variants (Table 2) (Arnhold et al, 2015; Babu et al, 2019; Bear et al, 2014; Bertolacini et al, 2012; Brauner et al, 2020; Flemming et al, 2013; França et al, 2013; Gregory et al, 2015; Juanes et al, 2016; Meng et al, 2019; Rahimov et al, 2006; Vaaralahti et al, 2012; Vishnopolska et al, 2021). This re‐evaluation was primarily based on population variant frequency in the gnomAD database (Karczewski et al, 2020).…”
Section: Clinical Reportmentioning
confidence: 99%